Transformations of the Tuva Autonomous Oblast under Soviet Union: the exhibits of the Tuva Regional Museum - Dyrtyk-ool, Anna O. (The New Research of Tuva, 2017)
The article examines the expositions of the Aldan Maadyr National Museum, Republic of Tuva (previously known as the Tuva Regional Museum), focusing on the changes in the region during the existence of Tuva Autonomous Oblast (1940s-1950s). The author analyzes the exhibition plans written by the museum personnel, which reveals the specifics of the museum work in Tuva and how it featured the national impetus of building Socialism.The Tuvan museum was required to actively promote the achievements of the best industrial enterprises, collective farms, best workers and cultural projects. The exhibits had to present a vivid image of the new society and a clear snapshot of the historical period. To stand up to the task, the museum went through a number of reforms, including setting up a new department of Socialist period in 1947.The permanent exhibits unavoidably featured copies of documents of the Soviet state, thematic materials on the life and work of V.I. Lenin and I.V. Stalin, on the rise of the Soviet power, its role in the development of Tuvan agriculture, electrification, and the improvements in education, medicine and culture. The articles provides economic data, lists of the best enterprises and workers in the region, and other useful information, illustrate by the photos preserved in the archives of the Aldan Maadyr Aldan Maadyr National Museum, Republic of Tuva.
Keywords: regional museum; exposition; Soviet history; history of Tuva; Tuvan Autonomous Oblast; Socialism